Managing the environmental friendly drilling fluids in petroleum industries - Ismail, Abdul Razak (Alkon Institute of Surabaya, Indonesia, 2001)
Drilling operation in the petroleum industries requires various types of drilling fluid systems. Some of the drilling fluids used are toxic and will create environmental problems when they were discharged to onshore or offshore environment. The disasters can be expected in the short term or long term effects. For normal drilling operation, a water-base drilling fluid which is less toxic are normally used. However, for certain condition or troublesome situations, oil-based drilling fluids will normally create short and long term disasters and therefore other alternatives are required. This paper discussed the comparison between the commercially oil-based drilling fluids and the laboratory formulated biodegradable Malaysian palm oil-based drilling fluid system. The study involved the basic properties and performance of the systems and the toxicity tests on marine organisms. The analyses for each of the system were presented. The results showed that the properties and performance of the new formulated ester, derived from Malaysian palm oil as the based drilling fluid system are comparable with the commercial drilling fluids. The analysis also showed that this new systems will reduce the environmental problems and will prevent the long term disaster to marine life.